Implementation of a spectrophotometer teaching and low cost: application in physics and chemistry laboratories fafism - Milagres, Kátia Isabel; Rodrigues Amaral, Camila; Santos, Érica Marques da Silva; B. Marques, Tarcísio; Gomes, Guilherme de Oliveira (Eclética Química, 2016)
The photometry in the visual field has wide application in analytical laboratories and research physical, chemical, biochemical, pharmacological, etc. It is essential that students of physics and chemistry have knowledge about this quantitative technique. One obstacle to the widespread use of this technique is the cost of equipment and materials to be used. The objective of this work is the introduction of a photometer didactic, whose construction and technique with a low operating cost and the easy using and producing results, as a practical solution to put school improvement. The features highlighted in the work do the proposed photometer an economically viable alternative tool for chemical analysis in the laboratories of the Faculty for research and / or teaching.